2018
DOI: 10.7748/nop.2018.e994
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control challenges of using a therapeutic robot

Abstract: This work was part of a National Institute for Health Research participatory action research and practice development study, which focused on the use of a therapeutic, robotic baby seal (PARO, for personal assistive robot) in everyday practice in a single-site dementia unit in Sussex. From the beginning of January 2017 until the end of September 2017, the cleaning and cleanliness of PARO was monitored through a service audit process that focused on the cleaning, amount of use and testing of contamination of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Paro has been evaluated and found to improve mood, improve engagement reduce stress (Rabbitt, Kazdin and Scassellati 2015) and improve quality of life (Joranson et al 2016). Concerns about infection control in clinical environments are unfounded; a recent study concluded that the Paro seal could be kept clean using biocide wipes (Dodds, Martyn and Brown 2018). Our experiences confirm that knowing Paro was artificial had no bearing on the perception that he was real.…”
Section: Use Of Technologymentioning
confidence: 60%
“…Paro has been evaluated and found to improve mood, improve engagement reduce stress (Rabbitt, Kazdin and Scassellati 2015) and improve quality of life (Joranson et al 2016). Concerns about infection control in clinical environments are unfounded; a recent study concluded that the Paro seal could be kept clean using biocide wipes (Dodds, Martyn and Brown 2018). Our experiences confirm that knowing Paro was artificial had no bearing on the perception that he was real.…”
Section: Use Of Technologymentioning
confidence: 60%
“…PARO has demonstrated benefits in reducing stress, anxiety, and antipsychotics use among older people with dementia [25][26][27]. However, there is a growing evidence base indicating the benefits, resistance and antipathy to using social robots in care settings [28]. There is a need for gaining an in-depth understanding towards the application of PARO, i.e., what worked, in which situation, and how.…”
Section: Effects Of Physical Appearance Of Robotsmentioning
confidence: 99%
“…We are aware of only two studies on infection control and Paro [32], only one of which reported a cleaning procedure based on use of the robot on a UK National Health Service (NHS) dementia ward for 9 months [33]. Dodds et al included a broad cleaning protocol discussing risk reduction measures and processes before, during and after use of Paro.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol described by Dodds et al [33], therefore, has limited quantitative microbiological support, as noted by Rowson and colleagues [34]. Furthermore, the research was limited only to Paro, that is reported to have anti-bacterial fur [37], thus restricting generalisability of results to a wider selection of companion robots that do not generally have anti-microbial coverings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation